Transformations of the Concept of Ideology in the Twentieth Century - KNIGHT, KATHLEEN (The American political science review, 2006)
Ideology has been the subject of a surprising amount of attention during the last half of the twentieth century. Although it has been argued that the term has been “thoroughly muddied by diverse uses” (Converse 1964, 207), an empirical investigation of the pages of the Review reveals substantial convergence among political scientists over time on a core definition. This essay traces the use of the concept in the Review since its launch in 1906. It reveals changing fashions in the connotation of the term, but suggests an underlying agreement on the essential components—coherence, stability and contrast—and underlines the centrality of the concept of ideology in political science.